LEGAL REVIEW OF THE CRIME OF HACKING CRYPTOCURRENCY BASED ON BLOCKCHAIN TECHNOLOGY - Abdul Kadir; Khozinatul Asrori (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2025)
Hacking cryptocurrencies (digital currencies that include Bitcoin, Ethereum, Litecoin, Ripple, Stellar, Dogecoin, Cardano, Eos, and Tron) is a serious challenge in the context of blockchain technology, threatening the security and trust of users and the system as a whole. This research aims to explore cryptocurrency hacking with a focus on blockchain technology. The first problem statement identifies the types of hacks that are common in cryptocurrency transactions, while the second problem statement explores the factors that influence the vulnerability of blockchain systems to hacking. The research method uses a normative research type, with a detailed literature study approach to hacking cases that have occurred before, as well as technical analysis of system weaknesses that allow hacking to occur. Data was collected from relevant primary and secondary sources to support the analysis. The outcome of this research is an in-depth understanding of how hacking mechanisms work in the context of blockchain, as well as the identification of risk factors that can be evaluated to strengthen blockchain security. The findings provide a foundation for practical advice for blockchain platform developers, cryptocurrency users, and regulators in an effort to improve the security of future blockchain infrastructure. It is hoped that the results of this study will not only improve the understanding of cryptocurrency hacking threats, but will also make a significant contribution to building a more secure and trustworthy blockchain ecosystem.